Editor’s Preface to the Commentaries about the Leininger Case - Houran, James (Journal of Scientific Exploration, 2022)
The popularity of ‘survival-related’ research over recent years has been accompanied by critical discussions by parapsychologists (e.g., Cunningham, 2012; Roll, 2006; Sudduth, 2009), as well as intense debates between advocates and skeptics (see e.g., Journal of Parapsychology, 80, pp. 169-264). Of course, these are not unexpected trends with highly controversial topics that can also challenge the belief systems of investigators and commentators. The correspondence below thus underscores the importance of methodology and rules of evidence relative to reincarnation-type cases.